Analysis of the energy barrier between Chlorella vulgaris cells and their interfacial interactions with cationic starch under different pH and ionic strength. (May 2020) - Wei, Chaoyang; Huang, Yun; Liao, Qiang; Xia, Ao; Zhu, Xun; Zhu, Xianqing
Graphical abstract: Highlights: Surface attachment of microalgae and cationic starch was successfully analyzed. Quantitative analysis of the interactions well agreed with the experiment data. Electrostatic attractive interaction played a determinative role in the attachment. Zeta potential based electrostatic interaction decreased with the descend of pH. There was no energy barriers between microalgae cells with pH of 3. Abstract: To explore the energy barrier between microalgae cells that impedes their aggregation and their interfacial interactions with cationic starch (CS), this study applied the extended Derjaguin Landau Verwey Overbeek (eDLVO) theory combined with the flocculation performance to analyze the interactions. The result shows that zeta potential based electrostatic interaction played a determinative role no matter for the energy barrier or the interfacial interactions. The energy barrier between microalgae cells would decrease with the descend of the pH and it disappeared when the pH decreased to 3 and resulted in self-flocculation. The quantitative analysis of the interfacial interactions between microalgae cell and CS showed well agreement with the experiment data of flocculation efficiency (FE) under different conditions of pH and ionic strength. Thus, the quantitative findings will be helpful to know the aggregation and flocculation process better and find more effective flocculants for microalgae harvesting.